Pengaruh Good Corporate Governance, Kepemilikan Konsentrasi dan Kepemilikan Manajerial terhadap Earnings Management (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Yosep Eka Putra (JURNAL PUNDI, 2020)
This study aims to determine the effect of good corporate governance, concentration ownership and managerial ownership on earnings management. The quality of corporate governance is measured using an index using instruments adopted from the corporate governance Perception Index (CGPI) issued by The Indonesian Institute of Corporate Governance (IICG). Ownership concentration is measured by the percentage of share ownership by individuals or groups outside of managers and the public. Managerial ownership is measured by the percentage of the company's common stock ownership by managers and commissioners. The analytical method used is multiple regression. This study uses empirical data from the Indonesia Stock Exchange (IDX) with a sample of 154 observations from 33 manufacturing companies. The results of the study showed a significant positive effect of ownership concentration on earnings management.Keywords : Good corporate governance; ownership concentration; managerial ownership; earnings management.